The response to double-dose hepatitis B vaccination in patients with HIV - Turken, Melda; Tatlı Kış, Tuba; Atalay, Sabri; Köse, Şükran (The European Research Journal, 2022)
Objectives: Prevention of hepatitis B virus (HBV) infection is necessary for patients with human immunodeficiency virus (HIV), since co-infection is associated with increased in mortality. The aim of this study was to investigate response to double-dose HBV vaccine in patients with HIV. Methods: A total of 149 patients with HIV were retrospectively evaluated. Sixty-eight patients who were HBV seronegative and administered double-dose HBV vaccine were included in the study. According to anti HBs levels, patients were evaluated in three groups: < 10 mIU/mL, 10-100 mIU/mL and ≥ 100 mIU/mL. Age, sex, transmission route, smoking, alcohol-substance abuse, comorbidities, CD4+ T cells counts and HIV viral load were compared in three groups. Results: The rate of response to HBV vaccination (anti HBs ≥ 10 mIU/mL) was 69.1%. Age was statistically significantly higher in the anti HBs < 100 mIU/mL group than in the anti HBs >100 mIU/mL group. The level of anti HBs was statistically significantly lower in patients with a CD4+ T cell count < 200 cells/μL (< 100 mIU/mL). Conclusions: The use of high-dose vaccine is a necessity as well as revaccination to improve vaccine immunogenicity in patients with HIV. In our study, low CD4+ T lymphocyte count and older age were found to have a negative effect on vaccine response.